Digital radiography in practice - Carroll, Quinn B. (Charles C Thomas, Publisher, Ltd., 2019)
Medical radiography programs will appreciate having an economical textbook that focuses on the practical aspects of digital radiography. Nearly all textbooks to date claiming the title ""digital radiography"" have dealt primarily with the managerial aspects of the topic at the expense of any practical information on how digital imaging works and its clinical implications for the daily practice of radiography. The goal of this book is to provide an accurate and adequate description of all the aspects of digital images and digital equipment, and their implications for radiographic technique and.